2021
DOI: 10.2169/internalmedicine.6316-20
|View full text |Cite
|
Sign up to set email alerts
|

Organizing Pneumonia as the First Presentation in a Patient with Takayasu Arteritis: A Report of Rare Complication

Abstract: A 48-year-old woman without any medical history visited an outpatient clinic with a chief complaint of cough persisting for more than 1 year and was diagnosed with organizing pneumonia. Computed tomography showed wall thickening with luminal stenosis of the main branch vessels of the aorta, and a detailed examination including fluorodeoxyglucose-positron emission tomography revealed Takayasu arteritis. There have been some reports of combined organizing pneumonia in similar vasculitis cases, but Takayasu arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It has been reported that the ocular involvements were found in 8.1%-68% [2] , non-specific arthralgia or myalgia in 13%-41%, aortic regurgitation in 5%-55%, coronary vessel stenosis in 25%, pulmonary hypertension in approximately 10%, cutaneous involvement in 3%-28%, and inflammatory bowel disease in 2.6% of TA patients [1] . Pneumonia as the primary manifestation is a rare presentation of TA [3][4][5] . We report a case of a young male patient who presented with blurry vision and antibiotic-unresponsive pneumonia, and was subsequently diagnosed with TA.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the ocular involvements were found in 8.1%-68% [2] , non-specific arthralgia or myalgia in 13%-41%, aortic regurgitation in 5%-55%, coronary vessel stenosis in 25%, pulmonary hypertension in approximately 10%, cutaneous involvement in 3%-28%, and inflammatory bowel disease in 2.6% of TA patients [1] . Pneumonia as the primary manifestation is a rare presentation of TA [3][4][5] . We report a case of a young male patient who presented with blurry vision and antibiotic-unresponsive pneumonia, and was subsequently diagnosed with TA.…”
Section: Dear Editormentioning
confidence: 99%
“…Pulmonary involvement in TA mainly consists of stenosis or occlusion of the pulmonary artery [1] . Other forms of pulmonary involvement are rare, such as pulmonary fibrosis, acute interstitial pneumonitis, parenchymal consolidations, and organizing pneumonia [3][4][5] . Our patient had bilateral opacities and consolidations that were unresponsive to antibiotics, but resolved after methylprednisolone, cyclophosphamide, and tocilizumab administrations.…”
Section: Dear Editormentioning
confidence: 99%